POD precursor film, POD-based graphite film and preparation methods of POD precursor film and POD-based graphite film

By introducing boron elements in the preparation process of the graphite film to form an anti-oxidation modified polymer, the problem of insufficient anti-oxidation performance of the graphite film in a high-temperature oxidation environment is solved, and the more stable and efficient performance of the graphite film in a high-temperature environment is achieved.

CN119842231AActive Publication Date: 2025-04-18YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202510329073.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

The existing graphite film has weak oxidation resistance under high-temperature oxidation environments, which affects its long-term use stability, and is especially restricted in the fields of aerospace, heat dissipation of electronic devices, etc.

Method used

By introducing boron aromatic compounds during POD polymerization and adding boron compounds during the solidification and molding of the film, the internal and external introduction of boron elements is achieved to form an antioxidant modified polymer, and the antioxidant performance of the graphite film is improved.

Benefits of technology

It significantly improves the oxidation resistance of graphite film, so that it can operate more stably in high temperature environments while maintaining high thermal conductivity, extend its service life, and improves its performance and reliability in multiple industry applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of heat-conducting graphite materials, in particular to a POD precursor film, a POD-based graphite film and a preparation method of the POD precursor film, the POD-based graphite film and the preparation method of the POD precursor film. After the reaction is finished, obtaining an antioxidant modified aromatic polyoxadiazole polymer solution; the preparation method comprises the following steps: coating an antioxidant modified aromatic polyoxadiazole polymer solution with a wiped film, then carrying out solidification forming in a multi-stage coagulation bath, and finally neutralizing, washing and drying to obtain a POD precursor film; the coagulating bath is an aqueous solution of sulfuric acid and boron compounds and an aqueous solution of sulfuric acid. And carrying out carbonization treatment and graphitization treatment on the POD precursor film to obtain the POD-based graphite film. According to the preparation method, the boron element is cooperatively introduced into and out of the POD precursor film, so that the oxidation resistance of the graphite film is remarkably improved while the high thermal conductivity is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a POD precursor film, a POD-based graphite film and a preparation method, and belongs to the technical field of thermal conductive graphite materials. Background Art

[0002] Graphite film has excellent thermal conductivity and structural stability, can effectively dissipate heat and withstand high temperature loads, and can be widely used as a thermal management material in high temperature environments. It plays an important role in industries with extremely strict thermal management requirements, such as aerospace, electronic equipment, and new energy vehicles.

[0003] Conventional industrial graphite film is mainly prepared by carbonizing and graphitizing polyimide (PI) film, and the technical process is relatively mature. However, with the continuous improvement of material performance requirements, PI-based graphite film has gradually shown limitations in thermal conductivity, conversion rate and other aspects. In comparison, POD (aromatic polyoxadiazole) has significant advantages as a precursor film in the preparation of graphite film. The high aromaticity and stable chemical structure of the POD molecule give it a higher carbon residual rate during carbonization and graphitization, reducing the generation of volatile by-products and ensuring higher material utilization. In addition, the volume shrinkage rate of the POD film is low, and the thickness can be effectively maintained. Coupled with the high density and thickness adjustability of its initial film structure, the thickness of the final prepared graphite film is significantly better than that of the graphite film with PI as the precursor film, which can reflect better thermal management capabilities.

[0004] However, in actual application, the stability of graphite film in high temperature environment is crucial. Although the graphite material itself has high thermal conductivity, its antioxidant performance is poor in an oxidizing atmosphere, and it is easy to undergo oxidative decomposition, which in turn affects its long-term stability. In many application scenarios, such as aircraft engine components, electronic device heat dissipation films, etc., graphite films are easily exposed to high-temperature oxidizing environments and must have excellent antioxidant properties to ensure that stable structures and performance can be maintained at extreme temperatures. The antioxidant capacity of POD-based graphite film in a high-temperature oxidizing environment is relatively weak, which limits its wide application under high temperature and high pressure conditions, especially its stability under long-term work or high oxygen atmosphere. Patent applications with publication numbers CN118419923A, CN117645296A, and CN117945758A all disclose methods for preparing related graphite films. These graphite films all have good thermal conductivity, but antioxidant performance is still a technical problem that needs to be urgently solved in this field. Summary of the invention

[0005] The present invention aims at the deficiencies in the prior art and provides a POD precursor film, a POD-based graphite film and a preparation method. An appropriate amount of boron aromatic compounds is introduced into the POD polymerization process to copolymerize with the POD precursor molecular chain to obtain an antioxidant modified polymer. Then, during the solidification and forming process of the film, a certain proportion of boron compounds is added to the solidification bath, and boron elements are further introduced into the film surface through a solvent replacement process, thereby obtaining a POD precursor film with internal and external synergistic antioxidant functions. Subsequently, the POD precursor film is converted into a POD-based graphite film with internal and external synergistic antioxidant properties through carbonization and graphitization treatment, and the POD-based graphite film has good thermal conductivity and antioxidant properties.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: a POD precursor film, first preparing an antioxidant modified polyarylene oxadiazole polymer solution, then further introducing antioxidant element boron on the film surface during the solution wet film forming process, and finally obtaining the POD precursor film through neutralization, washing and drying. The structural formula of the antioxidant modified polyarylene oxadiazole polymer is: ; The viscosity average molecular weight of the antioxidant modified polyaromatic oxadiazole polymer is 20000-80000 g / mol; x:y:z=(0.9-0.6):(0.1-0.5):(0.01-0.1).

[0007] The present invention also discloses a method for preparing a POD precursor film, the preparation method comprising: S1. Preparation of antioxidant modified polyaromatic oxadiazole polymer solution: Terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compounds are added to a fuming sulfuric acid system, polycondensation copolymerization reaction is carried out under heating conditions, and benzoic acid is added as a capping agent, and after the reaction is completed, an antioxidant modified polyaromatic oxadiazole polymer solution is obtained; S2. Preparation of POD precursor film: The antioxidant modified polyaromatic oxadiazole polymer solution prepared in step S1 is used to coat the scraping film, and then solidified in a multi-stage solidification bath, and finally neutralized, washed, and dried to obtain a POD precursor film; The coagulation bath is sulfuric acid, an aqueous solution of a boron compound and an aqueous solution of sulfuric acid, and the boron compound is at least one of boric acid and a boron salt.

[0008] Further, the hydrazine salt is selected from at least one of hydrazine sulfate and hydrazine hydrochloride; The boron aromatic compound is 3,5-dicarboxytriphenylborane; The boron salt is selected from at least one of borax, sodium metaborate, potassium borate, lithium borate, and 3,5-dicarboxytriphenylborate sodium.

[0009] Further, in step S1, the molar ratio of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compound is (5-8): (0.5-1.2): (1-2): (0.1-0.5); The ratio of the total mole number of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic hydrocarbon compounds to the mole number of benzoic acid is 1: (0.009-0.030).

[0010] Furthermore, in step S1, the specific preparation process of the antioxidant modified polyaromatic oxadiazole polymer solution is as follows: first, fuming sulfuric acid is added to the reactor, and terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compounds are added in sequence under stirring conditions. After complete dispersion, the temperature is raised to 70-90°C and stirred for 1h-2h, and then the temperature is continued to be raised to 120-140°C and stirred for 2-4h, benzoic acid is added as a capping agent, and the temperature is raised to 140-170°C and stirred for 0.5-2h, and then vacuum degassing is performed at 75-85°C to obtain an antioxidant modified polyaromatic oxadiazole polymer solution.

[0011] Furthermore, in step S2, the coagulation bath is a three-stage coagulation bath: The first coagulation bath is an aqueous solution of sulfuric acid and a boron compound. The total mass content of the boron compound and sulfuric acid in the first coagulation bath is 35-45%, and the mass ratio of sulfuric acid to the boron compound is (4-20):1; The second coagulation bath is an aqueous solution of sulfuric acid and boron compounds. The total mass content of the boron compounds and sulfuric acid in the second coagulation bath is 20-30%, and the mass ratio of sulfuric acid to the boron compounds is (4-25):1; The third coagulation bath is an aqueous solution of sulfuric acid, and the mass content of sulfuric acid in the third coagulation bath is 5-15%.

[0012] Furthermore, in step S2, the coagulation bath is a three-stage coagulation bath: the difference in mass content of boron compounds in two adjacent stages of coagulation baths is not greater than 5%; and the difference in mass content of sulfuric acid in two adjacent stages of coagulation baths is not greater than 15%.

[0013] The present invention also discloses a POD-based graphite film, which is obtained by subjecting the POD precursor film of the present invention to carbonization and graphitization.

[0014] The present invention also discloses a method for preparing a POD-based graphite film, the preparation method comprising: Carbonization treatment process: under argon protection, the POD precursor film is placed in a carbonization furnace, heated from room temperature to 200-300°C at a heating rate of 3-10°C / min for pre-oxidation treatment, and kept warm for 1-3h; then heated to 500-600°C at a heating rate of 2-5°C / min for low-temperature decomposition treatment, and kept warm for 1-3h; then heated to 1200-1500°C at a heating rate of 2-5°C / min for carbonization, and kept warm for 1-3h to obtain a POD carbonized film; The graphitization treatment process is as follows: under argon protection, the POD carbonized film is heated to 2000-2200°C at a heating rate of 3-10°C / min, kept warm for 1-3h, then heated to 2400-2500°C at a heating rate of 2-5°C / min, kept warm for 1-3h; then heated to 2600-3000°C at a heating rate of 2-5°C / min and kept warm for 1~3h, then slowly cooled to room temperature at a cooling rate of 3-10°C / min. During the cooling process, 1-5% mass concentration of oxygen is doped into the argon atmosphere to obtain the final POD-based graphite film.

[0015] The beneficial effects of the present invention are: The present invention achieves a graphite film that maintains high thermal conductivity while significantly improving its antioxidant properties by synergistically introducing boron elements inside and outside the POD precursor film. This performance improvement is mainly due to the multiple effects caused by boron atom doping: on the one hand, the introduction of boron atoms changes the electron cloud distribution on the surface of the graphite crystal, reduces the adsorption activity of oxygen molecules on the graphite surface, and thus effectively slows down the oxidation reaction rate; on the other hand, during the graphitization process, the BC covalent bonds formed by the combination of boron atoms and carbon atoms can further generate a stable boron oxide film under high temperature conditions. This film forms a physical barrier on the surface of the graphite film, effectively isolating oxygen, thereby enhancing antioxidant properties. In addition, boron doping reduces the scattering probability of phonons at lattice boundaries and defects by optimizing the microstructure of the graphite film, such as reducing crystal defects and improving lattice order, and improves phonon conduction efficiency. At the same time, the introduction of BC covalent bonds further enhances the overall stability of the carbon atom network, reduces the non-uniformity of the crystal vibration mode, and improves the phonon conduction path, thereby promoting the efficient propagation of heat energy in the film surface direction. To ensure the effect of boron doping, the present invention adopts the strategy of internal and external synergistic doping. The internal boron element is introduced through copolymerization reaction. The doping amount is small and the combination is firm, which can significantly optimize the microstructure of the graphite film and improve the thermal conductivity; the external boron element is introduced through solvent replacement, mainly distributed on the surface of the film, and forms a boron oxide film with antioxidant effect after graphitization, thereby further enhancing the antioxidant performance. At the same time, the present invention strictly controls the doping concentration and method of the boron element to avoid excessive or improper doping that destroys the lattice symmetry of the graphite film, resulting in increased phonon scattering and decreased thermal conductivity. Under this scientific design, the graphite film of the present invention achieves a good balance between high thermal conductivity and antioxidant properties, and has important application value.

[0016] The POD-based graphite film prepared by the present invention has excellent performance, with a thickness of 50-200 μm, a density of 1.9-2.2 g / cm³, a thermal conductivity of 1300-1800 W / (m·K), a thermal diffusion coefficient of 800-1000 mm² / s, and an oxidation induction time of 40-60 minutes at 200°C, showing excellent antioxidant ability and thermal management performance.

[0017] The POD-based graphite film of the present invention can be used in more severe environments. By introducing antioxidant elements on the surface and inside of the film, the antioxidant ability of the graphite film can be effectively enhanced and its service life can be extended without affecting its superior thermal conductivity and high conversion rate. Moreover, the surface of the film is uniform and flat, and there will be no powder falling problem. The antioxidant performance of the POD-based graphite film prepared by the preparation method of the present invention is improved, which can not only improve its stability in high temperature environments, but also promote its application in multiple industries such as aerospace, electronic heat dissipation, and energy conversion, providing a new research direction and technical breakthrough point for the development of the next generation of high-performance thermal management materials. DETAILED DESCRIPTION

[0018] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0020] A POD precursor film is provided. An antioxidant modified polyarylene oxadiazole polymer solution is first prepared. Then, during the wet film forming process of the solution, an antioxidant element boron is further introduced on the film surface. Finally, the POD precursor film is obtained by neutralization, washing and drying. The structural formula of the antioxidant modified polyarylene oxadiazole polymer is: ; The viscosity average molecular weight of the antioxidant modified polyaromatic oxadiazole polymer is 20000-80000 g / mol; x:y:z=(0.9-0.6):(0.1-0.5):(0.01-0.1).

[0021] The present invention also discloses a method for preparing a POD precursor film, the preparation method comprising: S1. Preparation of antioxidant modified polyoxadiazole polymer (POD) solution: Terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compounds are added to a fuming sulfuric acid system, polycondensation copolymerization reaction is carried out under heating conditions, and benzoic acid is added as a capping agent, and after the reaction is completed, an antioxidant modified polyaromatic oxadiazole polymer solution is obtained; S2. Preparation of POD precursor film: The antioxidant modified polyaromatic oxadiazole polymer solution prepared in step S1 is used to coat the scraping film, and then solidified in a multi-stage solidification bath, and finally neutralized, washed, and dried to obtain a POD precursor film; The coagulation bath is sulfuric acid, an aqueous solution of a boron compound and an aqueous solution of sulfuric acid, and the boron compound is at least one of boric acid and a boron salt.

[0022] Specifically, the hydrazine salt is selected from at least one of hydrazine sulfate and hydrazine hydrochloride; The boron aromatic compound is 3,5-dicarboxytriphenylborane; The boron salt is selected from at least one of borax, sodium metaborate, potassium borate, lithium borate, and 3,5-dicarboxytriphenylborate sodium.

[0023] More specifically, the structural formula of 3,5-dicarboxytriphenylborane is: .

[0024] The 3,5-dicarboxy triphenylborane is self-made, and the self-made method is as follows: (1) Add 3,5-dibromotoluene, tetrabutylammonium bromide (catalyst) and toluene (solvent) into a three-necked flask, stir and dissolve; add dimethyl sulfate dropwise, heat to 80°C, slowly add NaOH aqueous solution (provide the alkaline conditions necessary for the reaction); reflux for 12 hours; separate the liquids after cooling, dry the organic phase with anhydrous Na2SO4, and remove the solvent by rotary evaporation; purify by column chromatography to obtain 3,5-dibromo-p-xylene. (2) Dissolve 3,5-dibromo-p-xylene in concentrated H2SO4, add KMnO4 in batches under stirring, and control the temperature to <40°C; heat to 100°C, reflux for 6 hours until the purple color fades (generating MnO2 precipitate); filter while hot, cool the filtrate to room temperature, adjust the pH to 1 with concentrated hydrochloric acid, and precipitate a white precipitate; filter, wash with water, and recrystallize from ethanol / water (volume ratio 1:1) to obtain 3,5-dibromophthalic acid. (3) Dissolve 3,5-dibromophthalic acid in anhydrous THF, cool to -78°C (dry ice / acetone bath), slowly add n-BuLi dropwise, keep the temperature <-70°C, stir for 2 hours to obtain a deep red solution; add BF3·OEt2 dropwise, slowly warm to room temperature, stir for 12 hours, add dilute hydrochloric acid to quench the reaction, and extract with ethyl acetate; combine the organic phases, dry over anhydrous Na2SO4, and rotary evaporate to obtain a crude product of 3,5-dicarboxytriphenylborane; dissolve the crude product in THF / water (volume ratio 1:1), add dilute hydrochloric acid to pH = 2, precipitate, filter, and vacuum dry (40°C, 12 h) to obtain 3,5-dicarboxytriphenylborane.

[0025] Specifically, in step S1, the molar ratio of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compound is (5-8): (0.5-1.2): (1-2): (0.1-0.5); The ratio of the total mole number of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic hydrocarbon compounds to the mole number of benzoic acid is 1: (0.009-0.030).

[0026] More specifically, the equivalent concentration of the oleum is 115%, and the mass ratio of the total mass of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic hydrocarbon compounds to oleum is (0.05-0.15): (0.85-0.95).

[0027] Specifically, in step S1, the specific preparation process of the antioxidant modified polyarylene oxadiazole polymer solution is as follows: first, fuming sulfuric acid is added to the reactor, and terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compounds are added in sequence under stirring conditions. After complete dispersion, the temperature is raised to 70-90°C and stirred for 1h-2h, and then the temperature is continued to be raised to 120-140°C and stirred for 2-4h, benzoic acid is added as a capping agent, and the temperature is raised to 140-170°C and stirred for 0.5-2h, and then vacuum degassing is performed at 75-85°C to obtain an antioxidant modified polyarylene oxadiazole polymer solution.

[0028] Specifically, in step S2, the coagulation bath is a three-stage coagulation bath: The first coagulation bath is an aqueous solution of sulfuric acid and a boron compound. The total mass content of the boron compound and sulfuric acid in the first coagulation bath is 35-45%, and the mass ratio of sulfuric acid to the boron compound is (4-20):1; The second coagulation bath is an aqueous solution of sulfuric acid and boron compounds. The total mass content of the boron compounds and sulfuric acid in the second coagulation bath is 20-30%, and the mass ratio of sulfuric acid to the boron compounds is (4-25):1; The third coagulation bath is an aqueous solution of sulfuric acid, and the mass content of sulfuric acid in the third coagulation bath is 5-15%.

[0029] Specifically, in step S2, the coagulation bath is a three-stage coagulation bath: the difference in mass content of boron compounds in two adjacent stages of coagulation baths is not greater than 5%; and the difference in mass content of sulfuric acid in two adjacent stages of coagulation baths is not greater than 15%.

[0030] More specifically, the polyarylene oxadiazole polymer solution prepared in step S1 is poured onto a hot plate glass plate at 80-120°C to apply a scraper film at a certain thickness, and the wet film thickness is adjusted by adjusting the distance between the scraper and the glass plate, and the scraper coating thickness is 800-1500 mm; the coated wet film and the glass plate are placed in a first-stage coagulation bath for 5-10 minutes to solidify; the wet film is peeled off from the glass plate, and the wet film is placed in a second-stage coagulation bath for 10-20 minutes; the wet film is placed in a third-stage coagulation bath for 10-20 minutes; the completely solidified wet film is placed in an alkali solution for 20-40 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water and soaked for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 80-120°C for 30-60 minutes to obtain a POD precursor film with internal and external synergistic antioxidant properties.

[0031] More specifically, the alkali solution is a sodium hydroxide aqueous solution with a mass concentration of 1-5%.

[0032] The present invention also discloses a POD-based graphite film, which is obtained by subjecting the POD precursor film of the present invention to carbonization and graphitization.

[0033] The present invention also discloses a method for preparing a POD-based graphite film, the preparation method comprising: Carbonization process: under the protection of argon, the POD precursor film is placed in a carbonization furnace, and heated from room temperature to 200-300°C at a heating rate of 3-10°C / min for pre-oxidation treatment, and kept warm for 1-3 hours; then heated to 500-600°C at a heating rate of 2-5°C / min for low-temperature decomposition treatment, and kept warm for 1-3 hours; then heated to 1200-1500°C at a heating rate of 2-5°C / min for carbonization, and kept warm for 1-3 hours. At this time, the polymer is decomposed and a preliminary skeleton structure mainly composed of amorphous carbon is formed. At the same time, the doped boron element begins to react preliminarily with the carbon-based material to obtain a POD carbonized film; The graphitization treatment process is as follows: under argon protection, the POD carbonized film is heated to 2000-2200°C at a heating rate of 3-10°C / min, kept warm for 1-3h, then heated to 2400-2500°C at a heating rate of 2-5°C / min, kept warm for 1-3h; then heated to 2600-3000°C at a heating rate of 2-5°C / min and kept warm for 1~3h, then slowly cooled to room temperature at a cooling rate of 3-10°C / min. During the cooling process, 1-5% mass concentration of oxygen is doped into the argon atmosphere to promote the combination of boron element and oxygen on the surface of the film to generate boron oxide, forming a protective oxide film, and finally obtaining a POD-based graphite film with high thermal conductivity and synergistic internal and external antioxidant properties.

[0034] Example 1 S1: Preparation of POD solution: Terephthalic acid, isophthalic acid, hydrazine sulfate and 3,5-dicarboxytriphenylboron are dispersed and dissolved in 115% effective concentration fuming sulfuric acid. After each monomer is dissolved, the temperature is raised to 80°C and stirred for 1 hour, and then the temperature is further raised to 120°C and stirred for 2 hours. Benzoic acid is added as a capping agent, and then the temperature is raised to 150°C and stirred for 1 hour, and then the temperature is lowered to 80°C for vacuum degassing for 2 hours to obtain an antioxidant modified POD solution; wherein the molar ratio of terephthalic acid, isophthalic acid, hydrazine sulfate and 3,5-dicarboxytriphenylboron is 7.5:1.2:1:0.3, the ratio of the total molar number of terephthalic acid, isophthalic acid, hydrazine sulfate and 3,5-dicarboxytriphenylboron to the molar number of benzoic acid is 1:0.009, and the mass ratio of the total mass of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic hydrocarbon compounds to fuming sulfuric acid is 0.10:0.90.

[0035] S2: Preparation of POD precursor film: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 80°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a first-stage coagulation bath (a mixed aqueous solution of 32% mass concentration sulfuric acid and 8% mass concentration boric acid) for 8 minutes to solidify; the wet film is peeled off from the glass plate, and the wet film is placed in a second-stage coagulation bath (a mixed aqueous solution of 20% mass concentration sulfuric acid and 5% mass concentration boric acid) for 10 minutes; the wet film is then placed in a third-stage coagulation bath (a 10% mass concentration sulfuric acid solution) for 10 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 100°C for 40 minutes to obtain a POD film.

[0036] S3: Preparation of graphite film: The POD precursor film prepared in step S2 is subjected to a carbonization and graphitization process to obtain a graphite film.

[0037] The carbonization process is as follows: under argon protection, the POD precursor film is placed in a carbonization furnace, heated from room temperature to 300°C at a heating rate of 6°C / min for pre-oxidation treatment, and kept warm for 2 hours; then heated to 600°C at a heating rate of 3°C / min for low-temperature decomposition treatment, and kept warm for 2 hours; then heated to 1500°C at a heating rate of 3°C / min for carbonization, and kept warm for 2 hours.

[0038] The graphitization process is as follows: under argon protection, the POD carbonized film is heated to 2200°C at a heating rate of 10°C / min, kept warm for 3 hours, then heated to 2500°C at a heating rate of 5°C / min, kept warm for 3 hours; then heated to 3000°C at a heating rate of 5°C / min and kept warm for 3 hours, then slowly cooled to room temperature at a cooling rate of 10°C / min. During the cooling process, a 2% concentration of oxygen atmosphere is doped into the argon atmosphere to finally obtain a POD-based graphite film.

[0039] Example 2 The preparation method is the same as that in Example 1, except that in the preparation stage of the POD solution, some monomer ratios are changed, and the ingredients are prepared according to the recalculated weights of each monomer. The molar ratio of terephthalic acid, isophthalic acid, hydrazine sulfate, and 3,5-dicarboxytriphenylboron is 7.0:0.9:1.5:0.4, the ratio of the total molar number of terephthalic acid, isophthalic acid, hydrazine sulfate, and 3,5-dicarboxytriphenylboron to the molar number of benzoic acid is 1:0.015, and the mass ratio of the total mass of terephthalic acid, isophthalic acid, hydrazine salt, and boron aromatic hydrocarbon compounds to oleum is 0.15:0.95.

[0040] Example 3 The preparation method is the same as that of Example 1, except that in the preparation stage of the POD solution, some monomer ratios are changed, and the ingredients are prepared according to the recalculated weights of each monomer. The molar ratio of terephthalic acid, isophthalic acid, hydrazine sulfate, and 3,5-dimethyl 3,5-dicarboxy triphenyl boron is 6.5:0.8:1:0.4, the ratio of the total molar number of terephthalic acid, isophthalic acid, hydrazine sulfate, and 3,5-dicarboxy triphenyl boron to the molar number of benzoic acid is 1:0.012, and the mass ratio of the total mass of terephthalic acid, isophthalic acid, hydrazine salt, and boron aromatic hydrocarbon compounds to fuming sulfuric acid is 0.10:0.90.

[0041] Example 4 The preparation method is the same as that in Example 1, except that in the preparation stage of the POD solution, some monomer ratios are changed, and the ingredients are prepared according to the recalculated weights of each monomer. The molar ratio of terephthalic acid, isophthalic acid, hydrazine sulfate, and 3,5-dicarboxytriphenylboron is 7.5:1:1:0.5, the ratio of the total molar number of terephthalic acid, isophthalic acid, hydrazine sulfate, and 3,5-dicarboxytriphenylboron to the molar number of benzoic acid is 1:0.009, and the mass ratio of the total mass of terephthalic acid, isophthalic acid, hydrazine salt, and boron aromatic hydrocarbon compounds to oleum is 0.10:0.90.

[0042] Example 5 S1: The preparation method is the same as that of Example 1.

[0043] S2: Preparation of POD precursor film: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 80°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a first-stage coagulation bath (a mixed aqueous solution of 38% mass concentration of sulfuric acid and 2% mass concentration of boric acid) for 8 minutes to solidify; the wet film is peeled off from the glass plate, and the wet film is placed in a second-stage coagulation bath (a mixed aqueous solution of 24% mass concentration of sulfuric acid and 1% mass concentration of boric acid) for 10 minutes; the wet film is then placed in a third-stage coagulation bath (a sulfuric acid solution with a mass concentration of 10%) for 10 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 100°C for 40 minutes to obtain a POD film.

[0044] S3: The preparation method is the same as that of Example 1.

[0045] Example 6 S1: Preparation of POD solution: Disperse and dissolve terephthalic acid, isophthalic acid, hydrazine hydrochloride and 3,5-dicarboxytriphenylborane in 115% effective concentration fuming sulfuric acid. After each monomer is dissolved, heat to 70°C and stir for 2 hours, then continue to heat to 140°C and stir for 3 hours, add benzoic acid as a capping agent, then heat to 170°C and stir for 0.5 hours, then cool to 85°C and perform vacuum degassing for 2 hours to obtain an antioxidant modified POD solution; Among them, the molar ratio of terephthalic acid, isophthalic acid, hydrazine hydrochloride and 3,5-dicarboxytriphenylboron is 8:0.5:2:0.1, the ratio of the total moles of terephthalic acid, isophthalic acid, hydrazine hydrochloride and 3,5-dicarboxytriphenylboron to the moles of benzoic acid is 1:0.030, and the mass ratio of the total mass of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compounds to fuming sulfuric acid is 0.15:0.85.

[0046] S2: Preparation of POD precursor film: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 120°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a first-stage coagulation bath (a mixed aqueous solution of 40% mass concentration sulfuric acid and 5% mass concentration potassium borate) for 10 minutes to solidify; the wet film is peeled off from the glass plate, and the wet film is placed in a second-stage coagulation bath (a mixed aqueous solution of 28% mass concentration sulfuric acid and 2% mass concentration potassium borate) for 15 minutes; the wet film is then placed in a third-stage coagulation bath (a 15% mass concentration sulfuric acid solution) for 15 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 100°C for 40 minutes to obtain a POD film.

[0047] S3: Preparation of graphite film: The POD precursor film prepared in step S2 is subjected to a carbonization and graphitization process to obtain a graphite film.

[0048] The carbonization process is as follows: under argon protection, the POD precursor film is placed in a carbonization furnace, heated from room temperature to 300°C at a heating rate of 10°C / min for pre-oxidation treatment, and kept warm for 3 hours; then heated to 500°C at a heating rate of 2°C / min for low-temperature decomposition treatment, and kept warm for 3 hours; then heated to 1200°C at a heating rate of 5°C / min for carbonization, and kept warm for 3 hours.

[0049] The graphitization process is as follows: under argon protection, the POD carbonized film is heated to 2100°C at a heating rate of 5°C / min, kept warm for 2 hours, then heated to 2400°C at a heating rate of 2°C / min, kept warm for 3 hours; then heated to 2600°C at a heating rate of 3°C / min and kept for 3 hours, and then slowly cooled to room temperature at a cooling rate of 5°C / min. During the cooling process, a 1% concentration of oxygen atmosphere is doped into the argon atmosphere to finally obtain a POD-based graphite film.

[0050] Example 7 S1: Preparation of POD solution: Terephthalic acid, isophthalic acid, hydrazine hydrochloride and 3,5-dicarboxytriphenylborane are dispersed and dissolved in 115% effective concentration fuming sulfuric acid. After each monomer is dissolved, the temperature is raised to 90°C and stirred for 1 hour, and then the temperature is further raised to 120°C and stirred for 4 hours. Benzoic acid is added as a capping agent, and then the temperature is raised to 140°C and stirred for 3 hours, and then the temperature is lowered to 75°C and vacuum degassed for 2 hours to obtain an antioxidant modified POD solution; wherein The molar ratio of terephthalic acid, isophthalic acid, hydrazine hydrochloride and 3,5-dicarboxytriphenylboron is 5:1.2:1.5:0.2, the ratio of the total moles of terephthalic acid, isophthalic acid, hydrazine hydrochloride and 3,5-dicarboxytriphenylboron to the mole of benzoic acid is 1:0.020, and the mass ratio of the total mass of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic hydrocarbon compounds to oleum is 0.05:0.95.

[0051] S2: Preparation of POD precursor film: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 120°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a first-stage coagulation bath (a mixed aqueous solution of 30% mass concentration sulfuric acid and 5% mass concentration sodium metaborate) for 10 minutes to solidify; the wet film is peeled off from the glass plate, and the wet film is placed in a second-stage coagulation bath (a mixed aqueous solution of 17% mass concentration sulfuric acid and 3% mass concentration sodium metaborate) for 15 minutes; the wet film is then placed in a third-stage coagulation bath (a 5% mass concentration sulfuric acid solution) for 20 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 80°C for 60 minutes to obtain a POD film.

[0052] S3: Preparation of graphite film: The POD precursor film prepared in step S2 is subjected to a carbonization and graphitization process to obtain a graphite film.

[0053] The carbonization process is as follows: under argon protection, the POD precursor film is placed in a carbonization furnace, heated from room temperature to 250°C at a heating rate of 3°C / min for pre-oxidation treatment, and kept warm for 1 hour; then heated to 550°C at a heating rate of 5°C / min for low-temperature decomposition treatment, and kept warm for 1 hour; then heated to 1400°C at a heating rate of 2°C / min for carbonization, and kept warm for 1 hour.

[0054] The graphitization process is as follows: under argon protection, the POD carbonized film is heated to 2000°C at a heating rate of 3°C / min, kept warm for 1 hour, then heated to 2500°C at a heating rate of 3°C / min, kept warm for 1 hour; then heated to 2800°C at a heating rate of 4°C / min and kept for 2 hours, then slowly cooled to room temperature at a cooling rate of 3°C / min. During the cooling process, a 5% concentration of oxygen atmosphere is doped into the argon atmosphere to finally obtain a POD-based graphite film.

[0055] Comparative Example 1 S1: The preparation method is the same as that of Example 1, except that 3,5-dicarboxytriphenylborane is not added, and the quality of other raw materials remains unchanged.

[0056] S2: The preparation method is the same as that of Example 1, except that only sulfuric acid is used in the coagulation bath without adding boric acid. The specific process is as follows: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 80°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a first-stage coagulation bath (40% sulfuric acid solution) for 8 minutes to solidify; the wet film is peeled off from the glass plate and placed in a second-stage coagulation bath (25% sulfuric acid) for 10 minutes; the wet film is then placed in a third-stage coagulation bath (10% sulfuric acid solution) for 10 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 100°C for 40 minutes to obtain a POD film.

[0057] S3: The preparation method is the same as that of Example 1.

[0058] Comparative Example 2 S1: The preparation method is the same as that of Example 1, except that 3,5-dicarboxytriphenylborane is not added, and the quality of other raw materials remains unchanged.

[0059] S2: The preparation method is the same as that of Example 1.

[0060] S3: The preparation method is the same as that of Example 1.

[0061] Comparative Example 3 S1: The preparation method is the same as that of Example 1.

[0062] S2: Preparation of POD precursor film: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 80°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a first-stage coagulation bath (40% sulfuric acid solution) for 8 minutes to solidify; the wet film is peeled off from the glass plate and placed in a second-stage coagulation bath (25% sulfuric acid) for 10 minutes; the wet film is then placed in a third-stage coagulation bath (10% sulfuric acid solution) for 10 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 100°C for 40 minutes to obtain a POD film.

[0063] S3: The preparation method is the same as that of Example 1.

[0064] Comparative Example 4 S1: The preparation method is the same as that in Example 1, except that: in this comparative example 4, the addition ratio of 3,5-dicarboxytriphenylborane is increased, and in this comparative example 4, the molar ratio of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compound is 7.5:1.2:1:0.8; the amounts of other materials are the same as those in Example 1.

[0065] S2: The preparation method is the same as that of Example 1.

[0066] S3: The preparation method is the same as that of Example 1.

[0067] Comparative Example 5 S1: The preparation method is the same as that of Example 1.

[0068] S2: The preparation method is the same as that in Example 1, except that only one-stage coagulation bath is used in this comparative example 5. The specific process is as follows: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 80°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a coagulation bath (a mixed aqueous solution of 20% mass concentration sulfuric acid and 5% mass concentration boric acid) for 28 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize the acidic ions, and finally the wet film is soaked in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 100°C for 40 minutes to obtain a POD film.

[0069] S3: The preparation method is the same as that of Example 1.

[0070] Comparative Example 6 S1: The preparation method is the same as that of Example 1.

[0071] S2: The preparation method is the same as that in Example 1, except that the difference in boric acid concentration between adjacent coagulation baths is increased in this comparative example 6. The specific process is as follows: The POD solution prepared in step S1 is poured onto a hot plate glass plate at 80°C and coated with a film at a thickness of 1000 mm. The coated wet film and the glass plate are placed in a first-stage coagulation bath (a mixed aqueous solution of 30% mass concentration sulfuric acid and 10% mass concentration boric acid) for 8 minutes to solidify; the wet film is peeled off from the glass plate, and the wet film is placed in a second-stage coagulation bath (a mixed aqueous solution of 22% mass concentration sulfuric acid and 3% mass concentration boric acid) for 10 minutes; the wet film is placed in a third-stage coagulation bath (a 10% mass concentration sulfuric acid solution) for 10 minutes; the completely solidified wet film is placed in a 1% alkali solution for 30 minutes to neutralize acidic ions, and finally the wet film is placed in deionized water for more than 8 hours to remove the alkali solution, and the obtained wet film is dried at 100°C for 40 minutes to obtain a POD film.

[0072] S3: The preparation method is the same as that of Example 1.

[0073] Comparative Example 7 S1: The preparation method is the same as that of Example 1.

[0074] S2: The preparation method is the same as that of Example 1.

[0075] S3: The preparation method is the same as that in Example 1, except that during the carbonization process, the low-temperature decomposition treatment temperature is increased. The specific process is as follows: The carbonization process is as follows: under argon protection, the POD precursor film is placed in a carbonization furnace, heated from room temperature to 300°C at a heating rate of 6°C / min for pre-oxidation treatment, and kept warm for 2 hours; then heated to 700°C at a heating rate of 3°C / min for low-temperature decomposition treatment, and kept warm for 2 hours; then heated to 1500°C at a heating rate of 3°C / min for carbonization, and kept warm for 2 hours.

[0076] The graphitization process is as follows: under argon protection, the POD carbonized film is heated to 2200°C at a heating rate of 10°C / min, kept warm for 3 hours, then heated to 2500°C at a heating rate of 5°C / min, kept warm for 3 hours; then heated to 3000°C at a heating rate of 5°C / min and kept warm for 3 hours, then slowly cooled to room temperature at a cooling rate of 10°C / min. During the cooling process, a 2% concentration of oxygen atmosphere is doped into the argon atmosphere to finally obtain a POD-based graphite film.

[0077] The POD-based graphite films prepared in the above embodiments and comparative examples were subjected to performance tests, and the specific test results are shown in Table 1. The test methods involved are: (1) Thermal conductivity test: The thermal conductivity and thermal diffusivity of each sample were tested using the stable plate method.

[0078] (2) Oxidation induction time: The oxidation induction time of each sample was tested at 200°C using a pure oxygen atmosphere.

[0079] Table 1 POD-based graphite film performance test results

[0080] From the above table data, it can be seen that the POD-based graphite film prepared by the preparation method of the present invention in Examples 1 to 7 improves the anti-oxidation performance of the POD-based graphite film by synergistically improving the internal and external aspects, so that the POD-based graphite film has high thermal conductivity and diffusion coefficient while having good anti-oxidation performance. In addition, by matching appropriate coagulation bath conditions, the POD-based graphite film has good anti-oxidation performance and a smooth surface without powder loss, thereby further improving the comprehensive performance of the POD-based graphite film.

[0081] From the comparison of the experimental results of Comparative Example 1 and Example 1, it can be seen that if boron aromatic compounds and boron compounds are not added during the preparation of the POD-based graphite film, the anti-oxidation performance of the POD-based graphite film will be significantly reduced.

[0082] From the comparison of the experimental results of Comparative Example 2, Comparative Example 3 and Example 1, it can be seen that if no boron aromatic compounds are added during the preparation of the POD-based graphite film or no boron compounds are added during the solidification molding process, the oxidation resistance of the POD-based graphite film will be significantly reduced. Therefore, the coordinated introduction of boron elements inside and outside the POD precursor film is more conducive to the graphite film to significantly improve the oxidation resistance while maintaining high thermal conductivity.

[0083] From the comparison of the experimental results of Comparative Example 4 and Example 1, it can be seen that if the addition ratio of 3,5-dicarboxytriphenylborane is increased, too much boron element is introduced into the POD polymer, destroying the original structure of the polymer and resulting in reduced thermal conductivity.

[0084] From the comparison of the experimental results of Comparative Example 5 and Example 1, it can be seen that if only one-stage coagulation bath is used, the phase transition during the coagulation of the polymer solution is reduced, the phase change reaction is violent, resulting in an increase in internal defects of the film, and then powder falling occurs during the carbonization and graphitization process.

[0085] From the comparison of the experimental results of Comparative Example 6 and Example 1, it can be seen that if the difference in boric acid concentration between adjacent coagulation baths is increased, the performance of the final POD-based graphite film will be slightly affected. Therefore, the coagulation bath conditions defined in the present invention are more conducive to obtaining a POD-based graphite film product with better quality.

[0086] From the comparison of the experimental results of Comparative Example 7 and Example 1, it can be seen that: if the low-temperature decomposition treatment temperature is increased during the carbonization process, the boric acid or boron-containing groups are easily accelerated to dehydrate to generate B2O3, but the vapor pressure of B2O3 increases significantly at high temperatures, resulting in the loss of boron atoms through the gas phase, which ultimately affects the antioxidant properties of the POD-based graphite film. Therefore, the cooperation between the POD precursor film and the carbonization process conditions of the present invention is more conducive to obtaining a POD-based graphite film product with excellent comprehensive performance.

[0087] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0088] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A POD precursor film, characterized in that: First, an antioxidant modified polyarylene oxadiazole polymer solution is prepared, and then the antioxidant element boron is further introduced on the film surface during the solution wet film forming process, and finally the POD precursor film is obtained by neutralization, washing and drying. The structural formula of the antioxidant modified polyarylene oxadiazole polymer is: ; The viscosity average molecular weight of the antioxidant modified polyaromatic oxadiazole polymer is 20000-80000 g / mol; x:y:z=(0.9-0.6):(0.1-0.5):(0.01-0.1).

2. A method for preparing a POD precursor film according to claim 1, characterized in that: The preparation method is: S1. Preparation of antioxidant modified polyaromatic oxadiazole polymer solution: Terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compounds are added to a fuming sulfuric acid system, polycondensation copolymerization reaction is carried out under heating conditions, and benzoic acid is added as a capping agent, and after the reaction is completed, an antioxidant modified polyaromatic oxadiazole polymer solution is obtained; S2. Preparation of POD precursor film: The antioxidant modified polyaromatic oxadiazole polymer solution prepared in step S1 is used to coat the scraping film, and then solidified in a multi-stage solidification bath, and finally neutralized, washed, and dried to obtain a POD precursor film; The coagulation bath is sulfuric acid, an aqueous solution of a boron compound and an aqueous solution of sulfuric acid, and the boron compound is at least one of boric acid and a boron salt.

3. The method for preparing a POD precursor film according to claim 2, characterized in that: The hydrazine salt is selected from at least one of hydrazine sulfate and hydrazine hydrochloride; The boron aromatic compound is 3,5-dicarboxytriphenylborane; The boron salt is selected from at least one of borax, sodium metaborate, potassium borate, lithium borate and 3,5-dicarboxytriphenylborate sodium.

4. The method for preparing a POD precursor film according to claim 2, characterized in that: In step S1, the molar ratio of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compound is (5-8): (0.5-1.2): (1-2): (0.1-0.5); The ratio of the total mole number of terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic hydrocarbon compounds to the mole number of benzoic acid is 1: (0.009-0.030).

5. The method for preparing a POD precursor film according to claim 2, characterized in that: In step S1, the specific preparation process of the antioxidant modified polyaromatic oxadiazole polymer solution is as follows: first, fuming sulfuric acid is added to the reactor, and terephthalic acid, isophthalic acid, hydrazine salt and boron aromatic compounds are added in sequence under stirring conditions. After complete dispersion, the temperature is raised to 70-90°C and stirred for 1h-2h, and then the temperature is continued to be raised to 120-140°C and stirred for 2-4h, benzoic acid is added as a capping agent, and the temperature is raised to 140-170°C and stirred for 0.5-2h, and then vacuum degassing is performed at 75-85°C to obtain an antioxidant modified polyaromatic oxadiazole polymer solution.

6. The method for preparing a POD precursor film according to claim 2, characterized in that: In step S2, the coagulation bath is a three-stage coagulation bath: The first coagulation bath is an aqueous solution of sulfuric acid and a boron compound. The total mass content of the boron compound and sulfuric acid in the first coagulation bath is 35-45%, and the mass ratio of sulfuric acid to the boron compound is (4-20):1; The second coagulation bath is an aqueous solution of sulfuric acid and boron compounds. The total mass content of the boron compounds and sulfuric acid in the second coagulation bath is 20-30%, and the mass ratio of sulfuric acid to the boron compounds is (4-25):1; The third coagulation bath is an aqueous solution of sulfuric acid, and the mass content of sulfuric acid in the third coagulation bath is 5-15%.

7. The method for preparing a POD precursor film according to claim 2, characterized in that: In step S2, the coagulation bath is a three-stage coagulation bath: the difference in mass content of boron compounds in two adjacent stages of coagulation baths is not greater than 5%; and the difference in mass content of sulfuric acid in two adjacent stages of coagulation baths is not greater than 15%.

8. A POD-based graphite film, characterized in that: The POD-based graphite film is obtained by subjecting the POD precursor film according to claim 1 to carbonization and graphitization.

9. A POD-based graphite film according to claim 8, characterized in that: The POD-based graphite film has a thickness of 50-200 μm, a density of 1.9-2.2 g / cm³, a thermal conductivity of 1300-1800 W / (m·K), and a thermal diffusion coefficient of 800-1000 mm² / s.

10. A method for preparing a POD-based graphite film according to claim 8 or 9, characterized in that: The preparation method is: Carbonization treatment process: under argon protection, the POD precursor film is placed in a carbonization furnace, heated from room temperature to 200-300°C at a heating rate of 3-10°C / min for pre-oxidation treatment, and kept warm for 1-3h; then heated to 500-600°C at a heating rate of 2-5°C / min for low-temperature decomposition treatment, and kept warm for 1-3h; then heated to 1200-1500°C at a heating rate of 2-5°C / min for carbonization, and kept warm for 1-3h to obtain a POD carbonized film; The graphitization treatment process is as follows: under argon protection, the POD carbonized film is heated to 2000-2200°C at a heating rate of 3-10°C / min, kept warm for 1-3h, then heated to 2400-2500°C at a heating rate of 2-5°C / min, kept warm for 1-3h; then heated to 2600-3000°C at a heating rate of 2-5°C / min and kept warm for 1~3h, then slowly cooled to room temperature at a cooling rate of 3-10°C / min. During the cooling process, 1-5% mass concentration of oxygen is doped into the argon atmosphere to obtain the final POD-based graphite film.

Citation Information

Patent Citations

  • High-thermal-conductivity aromatic heterocyclic polymer-based graphite film and preparation method thereof

    CN117645296A

  • High-thermal-conductivity and high-strength aromatic heterocyclic polymer-based graphite film and preparation method thereof

    CN118419923A

  • Two step preparation of random polyoxadiazole copolymer and articles resulting therefrom

    CN101432339A

  • High-thermal-conductivity graphite film as well as preparation method and application thereof

    CN117945758A

  • Modified aromatic polyoxadiazole film as well as preparation method and application thereof

    CN119039586A

Cited By

  • High-thermal-conductivity high-residual-carbon aromatic heterocyclic polymer-based graphite film and preparation method thereof

    CN120535311A

  • POD-based high-thermal-conductivity graphite film as well as preparation method and application thereof

    CN121377001A

  • POD-based graphite film with interface affinity and preparation method thereof

    CN121554296A

  • POD-based graphite film with interface affinity and preparation method thereof

    CN121554296B